2001
DOI: 10.1093/hmg/10.10.1061
|View full text |Cite
|
Sign up to set email alerts
|

DCX in PC12 cells: CREB-mediated transcription and neurite outgrowth

Abstract: Mutations in doublecortin (DCX) result in X-linked lissencephaly in males. To explore the role of DCX in differentiation and signal transduction we overexpressed DCX in PC12 cells. Our results indicate that DCX stabilizes microtubules and inhibits neurite outgrowth in nerve growth factor-induced differentiation. However, neurite length is increased when differentiation is induced by epidermal growth factor and forskolin or by dibutyryl-cAMP. Furthermore, CREB-mediated transcription is downregulated, supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Taken together with the findings in previous reports, our data strongly suggest that PACAP-induced PKA activation results in the release of DCX from microtubules and that this released DCX associates with actin filaments through neurabin2 at the growth cone. cAMP-dependent neurite extension and axon formation are well known (52,53), but the detailed mechanism remains unclear. The PKA-regulated switching mechanism of DCX function between microtubules and actin filaments may be involved in neuronal migration and morphological change in response to extracellular cues.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the findings in previous reports, our data strongly suggest that PACAP-induced PKA activation results in the release of DCX from microtubules and that this released DCX associates with actin filaments through neurabin2 at the growth cone. cAMP-dependent neurite extension and axon formation are well known (52,53), but the detailed mechanism remains unclear. The PKA-regulated switching mechanism of DCX function between microtubules and actin filaments may be involved in neuronal migration and morphological change in response to extracellular cues.…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested that cofilin activity at axon tips is important for JIP3-enhanced axon elongation. However, many other JNK substrates, such as doublecortin (DCX), MAP2, the heavy subunit of the neurofilament protein (NFH), and superior cervical ganglia clone 10 (SCG10), have been reported to be important for neurite outgrowth (37,51,(53)(54)(55)(56). Whether these JNK substrates participate in the effect of JIP3 on axon elongation is worthy of further investigation.…”
Section: Jip3mentioning
confidence: 99%
“…The S47 residue has been mutated in several lissencephaly patients, 11,12,22 and overexpression of the mutated protein (S47R) abolished neurite outgrowth in PC12 cells. 23 If we assume that each of these five phosphorylation sites can be phosphorylated in an independent manner, then there are 2 5 (or 32) different combinatorial events. Although this may be an overestimation, it leaves us with numerous possibilities to explain the complex changes occurring in a migrating neuron.…”
Section: Modes Of Radial Migrationmentioning
confidence: 99%